The Forms of Legal Protection for Victims of Rape in Qanun Number 6, 2014 concerning Jinayat Law - Kalsum, Ummi; Ediwarman; Din, Mohd.; Ali, Dahlan (International Journal of Criminology and Sociology, 2021)
Victims are legally entitled to legal protection either indirectly or directly. One form of protection for rape victims as stated in Aceh Qanun Number 6 of 2014 concerning Jinayat Law is contained in Article 48 concerning indirect legal protection and Article 51 concerning direct legal protection in the form of restitution. However, in its implementation, victims have not received maximum legal protection. The forms of legal protection for rape victims in Qanun Number 6 of 2014 concerning the law of jinayat are in the form of indirect legal protection (in the abstract) and direct legal protection (in concreto). The lack of regulation causes direct legal protection for rape victims in Aceh Province has not been maximally obtained.